Exploring the Nature of Weak Chandra Sources near the Galactic Centre - Bandyopadhyay, R; Blundell, K; Podsiadlowski, P; Miller-Jones, J; Wang, Q; Brandt, W; Rappaport, S; Pfahl, E (2003)
We present early results from the first IR imaging of the weak X-ray sources discovered in a recent Chandra survey towards the Galactic Centre. From our VLT observations we will identify likely counterparts to a sample of the hardest sources in order to place constraints on the nature of this previously unknown population.